KONSTRUKSI CITRA CALON PRESIDEN JOKOWI PADA KAMPANYE PEMILIHAN PRESIDEN 2014 DI SURAT KABAR HARIAN JAWA POS - Wulan Fitria; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Successfulness of Jokowi in getting the first place in Indonesia is the turning point of his efforts in taking the public sympathy. Jokowi gets famous since the eSeMKa’s car and still gets mass media attention which is slowly make a good image for himself and finally nominated as one of president candidate. In the campaign period, Jawa Pos as the biggest mass media networks in Indonesia makes the Presidential Election 2014 as the media agenda by adding rubric about Presidential Election 2014. The aim from this research is to know the text structure of Jokowi’s campaign news as the presidential candidate in Jawa Pos Daily News and to know the journalist’s cognition and the reader’s cognition.This research is using the qualitative method with data collecting technique are documentation, book study and interview. Subjects of this research are the journalists and the chief editor of Jawa Pos Daily News. While the objects of this research are Jawa Pos’s news in the Presidential campaign 2014 during Juni-July with 10 news as the analysis unit. Data is analyzed by using peripheral analyse discourse with analysis model told by Van Dijk.Result of this research shows that (1) Presidential campaign 2014 news seen by the text structure shows the siding to Jokowi. This can be seen from the semantics and syntax element. (2)Cognition analysis of Jawa Pos’s journalist in Presidential Election campaign clearly shows uppermost percentage of a Jokowi-JK’s appearance. This can be seen from the syntax and stylistic element. There are too much the using of language style which can make Jokowi seen better than Prabowo. (3) Cognition analysis of Jawa Pos’s readers in Presidential Election 2014 news is not maximum yet in reporting the campaign because of some aspects. Such as the news portion which is not balance between the president candidate and vice president candidate.Keywords: Jokowi, Presidental Election, Image Construction, Discourse Analysis, Campaign, Agenda Setting Theory